Effects of differential jump training on balance performance in female volleyball players - Fuchs, P. X.; Fusco, A.; Cortis, C.; Wagner, H. (Applied Sciences, 2020)
The purpose of this study was to determine whether coordinative jump training that induces neuromuscular stimuli can affect balance performance, associated with injury risk, in elite-level female volleyball players. During the competitive season, the balance performance of 12 elite female players (highest Austrian division) was obtained via a wobble board (WB; 200 Hz) placed on an AMTI force plate (1000 Hz). Three identically repeated measurements defined two intervals (control and intervention phases), both comparable in duration and regular training. The intervention included 6 weeks of differential training (8 sessions of 15-20 min) that delivered variations in dynamics around the ankle joints. Multilevel mixed models were used to assess the effect on postural control. WB performance decreased from 27.0 ± 13.2% to 19.6 ± 11.3% during the control phase and increased to 54.5 ± 16.2% during the intervention (ß = 49.1 ± 3.5; p < 0.001). Decreased sway area [cm²] (ß = -7.5 ± 1.6; p < 0.001), anterior-posterior (ß = -4.1 ± 0.4; p < 0.001) and mediolateral sway [mm] (ß = -2.7 ± 0.6; p = 0.12), and mean velocity [mm·s-1] (ß = -9.0 ± 3.6; p < 0.05) were observed during the intervention compared with the control phase. Inter-limb asymmetry was reduced (ß = -41.8 ± 14.4; p < 0.05). The applied training concept enhanced balance performance and postural control in elite female volleyball players. Due to the low additional physiological loads of the program and increased injury risk during the competitive season, we recommend this intervention for supporting injury prevention during this period